Common and Unique Features in the Development of Startup Ecosystems in Latvia, Ukraine, and Georgia - Menshikov, Vladimir; Ruza, Oksana; Simakhova, Anastasiia; Bedianashvili, Givi (Comparative Economic Research. Central and Eastern Europe, 2025)
This research presents a comprehensive analysis and comparison of the startup ecosystems in Latvia, Ukraine, and Georgia. It identifies the key factors that foster their development and growth, and highlights the primary obstacles and challenges that confront startups in these countries. The authors used the following methods to achieve these objectives: correlation and regression analysis to examine funding trends and success factors, comparative analysis of key ecosystem parameters, as well as methods of analysis and synthesis. The novelty of the study lies in its identification of the most important factors that influence startup development in the three countries, the construction of a correlation and regression model of startup financing, and the comparative analysis of startup ecosystems. Comparing the startup ecosystems of the three countries revealed both common and unique features of each country, emphasizing how differences in political, economic, and cultural conditions shape startup development.